Палеогеографія території платформної України у кампанський вік - Якушин, Л.М.; Іщенко, І.І. (Інститут геологічних наук НАН України, 2009)
Выявлены особенности исторического развития, температурного и гидрологического режимов, условий седиментации кампанского морского бассейна территории платформенной Украины. The article deals with historical development, temperature and hydrological regimes, sedimentation conditions of Campanian sea basins in territory of platform Ukraine.